From "Talking Idly" to Realizing the Ben Ti of Knowledge and Action: Comments on Lederman's "What Is the 'Unity' in the 'Unity of Knowledge and Action'?". - Liu, Liangjian (Dao: A Journal of Comparative Philosophy, 2024)
Lederman makes a distinction between the ben ti 本體 ("original natural condition") of knowledge and action and the gong fu 工夫 ("training") of knowledge and action, associating "unity" with ben ti and "joint advancement" with gong fu. This essay argues that both "unity" and "joint advancement" are used to describe the ben ti of knowledge and action, and Wang Yangming 王陽明 emphasizes the unity of the ben ti and gong fu of knowledge and action. Yangming's doctrine of the ben ti of knowledge and action is ultimately for practical potency and should not be reduced to a theoretical philosophy of the truth about knowledge and action. Yangming's philosophy is for genuine knowledge of genuine knowledge and action. If Yangming's philosophy is genuine, it must be characterized by the unity of knowledge and action. In other words, the appropriate methodology to read Yangming must be the unity of knowledge and action.